Predictors of attitudes toward lesbian and gay parenting in an ecuadorian sample. - Hermosa-Bosano, Carlos (2021)
In the past few years, Ecuador has experienced legal changes toward the recognition of sexual minority rights. However, lesbian and gay (LG) individuals and couples still face legal obstacles to become parents and social barriers that place their families in disadvantage compared to their heterosexual counterparts. To date, it is not known whether the legal changes reflect society’s move toward a more progressive and accepting climate. This study analyzed the attitudes toward LG parenting in an Ecuadorian online-recruited sample. Three hundred thirty-eight (338) participants answered an online questionnaire about the negative effects and the benefits of having LG parents. The strongest belief among participants was that children of LG parents would be victimized because of their parents’ sexual orientation. Analyses indicated differences in attitudes based on age, sexual orientation, marital status, education level, as well as religiosity. Finally, regression models suggested that beliefs about the origins of sexual orientation and contact with LG people predicted attitude scores. Implications of these findings are discussed.